Effect of Aqueous Basil Extract (Ocimum sanctum) on Monosodium Glutamate-Induced Mice Sperm - Aris Soewondo; Sri Rahayu; Agung Pramana Warih Marhendra; Nurul Shafa Paramita; Anaqoh Roudhotul Jannah Winarso (Biotropika: Journal of Tropical Biology, 2025)
This study aims to analyse the protective effect of aqueous extract of basil leaves (Ocimum sanctum) on the sperm quality of monosodium glutamate (MSG)-induced mice. This study used 30 male mice (aged 4-5 weeks old and weighing 25-35 grams), which were then randomly divided into five groups: P0 (healthy male mice), P1 (male mice induced with 4mg/kg BW MSG), P2, P3, P4 (male mice induced with MSG and given aqueous extract of basil leaves (O. sanctum) 300mg/kgBB, 500mg/kgBB, 700mg/kgBB for 14 days). At the end of treatment, all mice will be sacrificed and cauda epididymis was isolated. The obtained semen was analysed for sperm quality, including motility, viability, concentration, and spermatozoa abnormalities. Data analysis used one-way ANOVA and continued with the Duncan test using SPSS for Windows. In this study, the administration of 700mg/kg BW aqueous extract of basil leaves (O. sanctum) could improve sperm quality by increasing motility, viability, and concentration of sperm and also alter the sperm abnormality of MSG-induced mice.